ANALYSIS OF READINESS TO USE OF E-TICKETING APPLICATIONS, PERCEPTION OF SERVICE USERS AND PORT ORGANIZERS AT TELUK BUNGUS FERRY PORT, WEST SUMATERA PROVINCE - Ilham, Chairul Insani; Yulianto, Andri; Wasianto, Wawan; Latuheru, Paulina M; Putri, Septina Odelina (IWTJ : International Water Transport Journal, 2024)
Bungus Bay Ferry Port is a very important commercial port to connect the city of Padang with the Mentawai Islands via waterways. The ticket purchase process at Bungus Bay Ferry Port still uses a manual system, by queuing and waiting for a long time at the port counter, making it difficult for service users because there is no e-ticketing application or cashless method. This study aims to analyze the readiness of the perception of service users and port organizers if the use of the e-ticketing application is implemented in purchasing tickets at Bungus Bay Ferry Port, West Sumatra Province. This study uses a quantitative approach research type with analysis using a questionnaire method in the form of distributing digital questionnaires/google forms and interview methods as data collection tools and direct observation methods in the field. Based on the perception of service users and port organizers, the results of the readiness analysis were obtained, namely with a percentage of 84.8% of service users and 87.5% of port organizers having readiness in using the e-ticketing application at the Teluk Bungus Ferry Port. For this reason, service users should start preparing to learn more and seek information about online ticket reservations so that when implemented they can easily access online ticket reservations independently. For Port Organizers, they should start preparing everything, starting from IT infrastructure and networks as well as an understanding of online ticket reservations.